Differences in fracture resistance after root canal irrigation using guava leaf extract (Psidium guajava L.) and lime juice (Citrus aurantifolia): Perbedaan ketahanan fraktur setelah irigasi saluran akar dengan menggunakan ekstrak daun jambu biji (Psidium guajava L.) dan air perasan jeruk nipis (Citrus aurantifolia) - Nurfadhillah Arifin; Risnayanti Anas; Nursakia (Makassar Dental Journal, 2022)
After root canal treatment, teeth are at higher risk of fracture than vital teeth; the cause is multifactorial, both iatrogenic and non-iatrogenic. Guava are often usedbecause the leaves have been proven to treat various diseases. Guava leaves contain active ingre-dients, including tannins, flavonoids, essential oils and saponins.Lime is often processed by the community as a fresh drink, such as warm lime juice. Lime fruit has useful ingredients such as essential oils, citric acid, amino acids and saponins. The aim of this study was to analyze differences in fracture resistance after root canal irrigation between 60% GL extract and 100% lime juice. This is a laboratory experiment using extracts of GL, LJ, maxillary central incisor with a post-test only control group design, which was tested statistically by using one-way Anova followed by a post hoc test. Fracture resistance in the 60% GL extract group averaged is 45.07±9.80; while the 100% LJ group is40.86±12.71; the differ is 4,280. It was concluded that there is no significant difference in the degree of fracture resistance between the 60% GL and 100% LJextract groups as root canal irriga-gation materials.